Olfactory disorder in patients infected with SARS-CoV-2 - Yen, Yung-Feng (J Microbiol Immunol Infect, 2021)
Three (60%) of five patients with coronavirus disease 2019 (COVID-19) had olfactory disorder. Two exhibited anosmia at the onset of COVID-19, while one had hyposmia 4 days after the onset of COVID-19. All patients with olfactory disorder were completely recovered with a mean recovery length of 11.3 days.